2017
DOI: 10.5696/2156-9614-7.15.8
|View full text |Cite
|
Sign up to set email alerts
|

Status of Air Pollution in Botswana and Significance to Air Quality and Human Health

Abstract: Background.Air pollution is an important issue in developed and industrialized countries. The most common sources of air pollution are anthropogenic activities such as construction dust, vehicular emissions and mining. For low- and middle-income countries, biomass burning and indoor heating are the leading sources of air pollution. As more of the world undergoes development and human populations increase, industrialization is also increasing, along with the potential for air pollution.Objectives.This article r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that several studies in other environments, such as residential homes, bakeries and school buildings, have been conducted in Africa (Jafta et al 2017 ). Highlights of the studies are documented in Table S1 , including Uganda (villages) (Nakora et al 2020 ), Malawi (households) (Rylance et al 2019 ), Côte d’Ivoire (homes) (Kouao et al 2019 ), Ethiopia (homes) (Downward et al 2018 ), South Africa (homes) (Jafta et al 2017 ), Botswana (national review) (Wiston 2017 ), Kenya (homes) (Yip et al 2017 ), Nigeria (homes) (Mbanya and Sridhar 2017 ), Nepal, Kenya and Sudan (homes) (Bikram et al 2011 ). In comparison with Nigerian studies, a study carried out in six villages in Uganda showed that PM exceeded the WHO limit (Nakora et al 2020 ), and CO was above the threshold in forty-five households in Kenya (Yip et al 2017 ) and Uganda (Nakora et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that several studies in other environments, such as residential homes, bakeries and school buildings, have been conducted in Africa (Jafta et al 2017 ). Highlights of the studies are documented in Table S1 , including Uganda (villages) (Nakora et al 2020 ), Malawi (households) (Rylance et al 2019 ), Côte d’Ivoire (homes) (Kouao et al 2019 ), Ethiopia (homes) (Downward et al 2018 ), South Africa (homes) (Jafta et al 2017 ), Botswana (national review) (Wiston 2017 ), Kenya (homes) (Yip et al 2017 ), Nigeria (homes) (Mbanya and Sridhar 2017 ), Nepal, Kenya and Sudan (homes) (Bikram et al 2011 ). In comparison with Nigerian studies, a study carried out in six villages in Uganda showed that PM exceeded the WHO limit (Nakora et al 2020 ), and CO was above the threshold in forty-five households in Kenya (Yip et al 2017 ) and Uganda (Nakora et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some published meta-analyses have shown positive association between air pollution exposure and T2DM [24][25][26][27][28] . The major sources of air pollutants are vehicular exhaust and construction activities in developed countries and continuous burning activities in developing countries [1,57] . The quantity of ground testing of PM2.5 also varies between developed and developing countries [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Masons have a very high risk of being exposed to air pollution [3,4]. According to research data in 2010, more than 50% of masons are regularly exposed to air pollution such as steam, gas, dust, or smoke in the workplace [5].…”
Section: Introductionmentioning
confidence: 99%